O uso de tecnologias digitais e o papel do vendedor em vendas relacionais no B2B - Moura, Cristiano Rodrigues de (2022)
The adoption of digital technologies is absorbed more quickly in the business-to-consumer market (B2C) than to business-to-business market (B2B). From the perspective of academic studies, the focus has been on B2C. However, even if more slowly, digital technologies entered the B2B market and were leveraged from 2020 onwards due to the Covid 19 pandemic. Before, commercial relationships took place almost exclusively in person between sellers and buyers, and a good relationship between these actors would possibly direct the choice for a particular supplier, which ended up being an indicator of success in the partnership. With the occurrence of social isolation, communication became entirely virtual, through the most diverse digital technologies. The ease of access to information available on the internet about products, services and prices made B2B buyers to carry out their transactions on digital platforms without the interference of a human in the entire process. In this scenario, this research consisted of understanding the influence of digital technologies on the role of the seller in a context of relational sales specifically in the pneumatic and electronics industrial automation market. The qualitative approach research, through interviews, collected the perception of 12 sellers and 3 buyers, generating a corpus of 122 transcribed pages. Qualitative data analysis was used to organize, interpret and conclude the findings. The study showed that relational selling lacks three key elements: trust, transparency and honesty from the seller's perspective. From the buyers' perspective, two key elements are repeated, trust and transparency, complemented by availability and a sense of urgency. Such elements must be supported by a seller's attitude that emphasizes knowledge about the product/service offered and empathy for the buyer's needs. With regard to digital technologies, all respondents were unanimous in saying that there will be no setback and that it is necessary to use it in their daily lives. They are important tools for optimizing time and processes, leaving salespeople with free time to dedicate themselves to demands that bring greater added value to their companies and also to their customers. The present research allowed to corroborate previous studies on relational sales, as well as adding new knowledge that clarifies the role of the salesperson in light of the adoption of digital technologies in a pandemic context.